Proton Magnetic Resonance Spectroscopy (1H-MRS)-Based Neurometabolite Levels and Cognitive Function in Relation to Visceral Obesity and Non-Alcoholic Fatty Liver Disease (P14-019-19). (13th June 2019) - Pilande, Emmalyn; So, Shirley; Lim, Unhee; Hullar, Meredith; Wilkens, Lynne; Shepherd, John; Albright, Cheryl; Lampe, Johanna; Marchand, Loïc Le; Ernst, Thomas; Chang, Linda
Abstract: Objectives: Intra-abdominal adiposity in the viscera and liver, compared to total adiposity, carries a higher metabolic risk, and it varies substantially by sex and race. We examined the association of neurometabolites and cognitive function with visceral obesity and non-alcoholic fatty liver disease (NAFLD) in multiethnic older adults. Methods: The Multiethnic Cohort Brain-Gut-Adiposity Study included 100 participants aged 61–77 years, who were recruited into balanced strata by sex, ancestry (Japanese, Native Hawaiian or white) and body mass index (BMI) levels (range: 18.0–44.9 kg/m 2 ). We measured the concentration of key brain metabolites in the frontal and parietal gray matter (GM) and frontal white matter using 1 H-MRS and assessed cognitive function using the Modified Mini-Mental State (3MS) and the NIH Toolbox (NIHTB) tests. Mean neurometabolite levels and cognition scores were compared by visceral obesity (visceral fat area at L1-L5 > 150 cm 2 ) and NAFLD (liver fat >5.0%) status determined by abdominal MR imaging, while adjusting for age, sex, race, education, dual energy X-ray absorptiometry-based total adiposity and other confounders. Results: The prevalence of visceral obesity was 52%, NAFLD 32%, and both conditions 27%. Participants with visceral obesity had higher adjusted mean levels of total glutamate [11.6 (11.3, 12.0) vs. 10.8 (10.4, 11.2) mM/kg; P  = 0.01] and myo-inositol [5.2 (5.0, 5.4) vs. 4.7 (4.6, 4.9) mM/kg; P  = 0.004] in the parietal GM but had similar levels of total choline, total creatine and N-acetylaspartate. NAFLD status was not significantly associated with the levels of neurometabolites. No significant interaction was detected between the two conditions: participants with either condition compared to those with neither showed a trend toward higher levels of myo-inositol [5.2 (4.9, 5.5) vs. 4.8 (4.5, 5.0) mM/kg; P  = 0.07]. Further, participants with NAFLD scored lower for crystallized cognition for language [113 (110, 117) vs. 118 (116, 120); P  = 0.02], in particular for reading ability [113 (109, 117) vs. 119 (117, 123); P  = 0.03]. Conclusions: Results of this comprehensive, pilot imaging study suggest that, regardless of total adiposity and race/ethnicity, high visceral adiposity is associated with elevated concentrations of inflammatory neurometabolites, and NAFLD is associated with reduced language abilities. Funding Sources: National Institutes of Health (National Institute of Diabetes and Digestive and Kidney Diseases and National Cancer Institute).